2021
DOI: 10.1177/0975087820987174
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Quality and Trade Flow: Empirical Evidence from Malaysia and Other OIC Member Countries in Africa

Abstract: This article examines the impact of institutional quality on bilateral trade flow between Malaysia and selected 25 African Organisation of Islamic Cooperation (OIC) member countries. Four institutional qualities were selected from World Governance Indicators with other trade predictors from the period from 1985 to 2016. Using gravity model of trade and Poisson pseudo-maximum likelihood estimation method (PPML) technique, the results confirm that government effectiveness, regulatory quality and political stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…To address the heteroskedasticity and the zero-trade issue literature has widely criticized the OLS, Fixed and Random effects model, and preferred PPML technique (Silva and Tenreyro, 2006;Braha et al, 2018;Brodzicki and Uminski, 2018;Correia et al, 2020;Yusuf et al, 2021;Santos Silva and Tenreyro, 2022). PPML has several advantages over other estimators and effectively addresses the common issue in trade analysis (Anderson and Yotov, 2016;Yotov et al, 2016). Hence, we rely on the results of estimates obtained from the PPML technique.…”
Section: Estimation Protocolmentioning
confidence: 99%
“…To address the heteroskedasticity and the zero-trade issue literature has widely criticized the OLS, Fixed and Random effects model, and preferred PPML technique (Silva and Tenreyro, 2006;Braha et al, 2018;Brodzicki and Uminski, 2018;Correia et al, 2020;Yusuf et al, 2021;Santos Silva and Tenreyro, 2022). PPML has several advantages over other estimators and effectively addresses the common issue in trade analysis (Anderson and Yotov, 2016;Yotov et al, 2016). Hence, we rely on the results of estimates obtained from the PPML technique.…”
Section: Estimation Protocolmentioning
confidence: 99%
“…Their findings revealed that the institutional quality is a significant factor in enhancing export while GDP of imported countries and weighted distance showed the positive and negative effects on exports, respectively, as depicted by gravity model. In a recent study, Yusuf, Afolabi, Shittu, Gold, and Muhammad (2021) analyzed the effect of governance indicators on bilateral trade flows between Malaysia and selected African OIC countries. Their empirical outcomes revealed that the poor institutional quality in African countries adversely affect the bilateral trade flows among OIC member countries in Africa.…”
Section: Institutional Quality and Trade Flowsmentioning
confidence: 99%
“…The study also observed a shift in the composition of trade from primary commodities to manufactured goods, suggesting a potential move towards greater economic diversification among OIC member countries. Yusuf et al (2021) investigated the correlation between trade flows among OIC member countries and the quality of institutions, specifically in Malaysia and other African OIC member nations. The study employed fixed and random effect models and utilized panel data from 2000-2018.…”
Section: Muslim Business Andmentioning
confidence: 99%